MATERNITY PROTECTION IN THE LABOR MARKET ARISING FROM THE EFFECTIVENESS OF THE PRINCIPLES OF HUMAN DIGNITY AND EQUALITY (CIPEEX, 2025)
The objective of this study is to analyze the effectiveness of maternity protection provided for in the Brazilian legal system as a means of materializing the principle of human dignity. The permanence of working mothers in the job market is made possible through protections granted by the Federal Constitution and labor legislation. Using the literature review method, this study identifies numerous challenges to preventing maternal exclusion from formal employment. It also highlights how women occupy fewer positions due to their susceptibility to pregnancy, which often deters employers. The principle of human dignity positions human beings at the center of the Democratic Rule of Law, requiring respect for their rights and guarantees. Furthermore, the principle of equality ensures that women and mothers are treated on equal terms with men, prohibiting discrimination. The study concludes that without specific legislation, working mothers face significant barriers to entering or remaining in the formal job market. The responsibilities associated with pregnancy and caregiving often lead to discrimination and resistance from employers, both in hiring and contract retention.
Keywords: Maternity; Human dignity; Equality; Labor Law